Ductal carcinoma in situ of the breast - Jennifer L. Peterson; Laura A. Vallow; Stephanie L. Hines; Steven J. Buskirk (Frontiers Media S.A., 2011)
Ductal carcinoma in situ (DCIS) of the breast is a noninvasive form of breast cancer that has increased in incidence over the past several decades secondary to screening mammography. DCIS now represents 20-30% of all newly diagnosed cases of breast cancer. Patients with DCIS typically present with an abnormal mammogram, and diagnosis is most commonly obtained with an imageguided biopsy. Historically, mastectomy was considered the primary curative option for patients with DCIS. However, treatment of DCIS continues to evolve, and now treatment strategies also include breast-conserving therapy, which consists of local excision followed by radiation therapy or local excision alone. Multiple randomized trials have confirmed a decrease in ipsilateral breast tumor recurrence in patients treated with local excision followed by radiation therapy compared with local excision alone. Ongoing clinical trials attempt to identify a subgroup of DCIS patients at low risk for recurrence who may not benefit from radiation therapy. In addition, because the majority of ipsilateral breast tumor recurrences occur near the original primary tumor site, partial breast irradiation is currently under investigation as a treatment option for DCIS patients. Randomized trials have shown tamoxifen can reduce the risk of ipsilateral and contralateral breast tumor recurrences while the role of aromatase inhibitors is the subject of current clinical trials. DCIS represents a complex pathologic entity, and treatment optimization requires a multidisciplinary approach.